A jogosulatlan pénzügyi tevékenység megítélése a közjegyzői gyakorlatban és összefüggése az okirat hamisítással - Hodosi, Gábor (Debreceni Jogi Műhely, 2017)
The unlawful providers destroy the trust, as well as in the lawful providers in the whole financial system. The adjudgement of the loan service by non financial providers can cause problem in the notarial practice. Namely the notary can just conclude of the frequency, for-profitnature and organization of the loan service provided by the parties statements.My present study gives a summary about the criminal facts and their analysis occur in the practice as well as to the notarial bench, who can be seen as non-proffessional connected to the criminal education. The article provides useful information, the reader gets an opportunity to analyse the unlawful financial service from the notarial aspect.